GERAKAN PEREMPUAN DI INDONESIA DARI MASA KE MASA: SEJARAH, HAMBATAN DAN PENCAPAIAN - Lupyta Agra Divina; Laila Khalid Alfirdaus; Fitriyah - - (Journal of Politic and Government Studies, 2021)
The Women's Movement in Indonesia has a long journey in advocating for the women’s interest. In its movement, the Indonesian women's movement has a long history which in this study will be discussed through the periodization of politics from the pre-independence era to the post-reform era. In addition, this research also presents the obstacles and achievements of the women's movement in Indonesia in each period. This study aims to analyze the history of the women's movement in Indonesia and its obstacles and achievements. To analyze this, this study uses a qualitative method with data collection techniques through literature and documentation studies. Through the long history of the Indonesian women's movement, the Indonesian women's movement is still moving and is faced with obstacles in advocating in the name of women's interests.